2017
DOI: 10.1163/22134468-00002088
|View full text |Cite
|
Sign up to set email alerts
|

Has it really Been that Long? Why Time Seems to Speed up with Age

Abstract: The impression that time speeds up with age is a well known phenomenon. In the literature, a number of theories on this age effect exists, but results of the respective studies are inconclusive, and even somewhat paradoxical: The age effect occurred only when speed of time was judged for periods in the past. However, usually no difference was found when comparing present time perception between participants in different age groups. Our investigation had two aims: To begin, we tried to solve the riddle of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 2 publications
2
14
1
Order By: Relevance
“…Although it was not a study goal, we found that the two different ratings of time passage did not correlate with age. The low number of middle-aged and older adults (N = 52) makes this finding unreliable, but it is important to note that it is consistent with the literature that has shown with both WEIRD (Friedman & Janssen, 2010;Winkler et al, 2017;Wittmann & Lehnhoff, 2005) and non-WEIRD (Janssen et al, 2013) samples that, unless one uses ten-year intervals, there is no relation between age and the subjective experience of time in cross-sectional comparisons.…”
Section: Laypeople's Beliefs and Their Time Experience Reports -16supporting
confidence: 59%
See 4 more Smart Citations
“…Although it was not a study goal, we found that the two different ratings of time passage did not correlate with age. The low number of middle-aged and older adults (N = 52) makes this finding unreliable, but it is important to note that it is consistent with the literature that has shown with both WEIRD (Friedman & Janssen, 2010;Winkler et al, 2017;Wittmann & Lehnhoff, 2005) and non-WEIRD (Janssen et al, 2013) samples that, unless one uses ten-year intervals, there is no relation between age and the subjective experience of time in cross-sectional comparisons.…”
Section: Laypeople's Beliefs and Their Time Experience Reports -16supporting
confidence: 59%
“…One explanation that is sometimes mentioned in the literature (Joubert, 1983;Quinn & Reznikoff, 1985;Winkler et al, 2017) and twice in the survey was that older adults feel that they are running out of time. Another belief about the cause of the phenomenon was that older adults focus more on the past and reflecting upon the past makes time feel like it has passed quickly.…”
Section: 4%mentioning
confidence: 99%
See 3 more Smart Citations